Pengaruh Konsentrasi Minyak Nabati terhadap Lama Simpan dan Kualitas Pasta Bawang Merah (Allium ascalonicum L.) - Celvia Carlinawati Ndruru; Maria Marina Herawati (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2021)
Shallots (Allium ascalonicum L.) have a short shelf life because these tubers can experience decay and premature germination. Therefore, innovation is needed in shallot processing, one of which is by processing shallots into pasta products. This research conducted the making of onion paste with the addition of vegetable oil to improve the quality of the paste. The purpose of this study was to examine the effect of vegetable oil concentration treatment on shelf life and quality of shallot paste and to determine the level of preference for the panelists to shallot paste by organoleptic test. This study used a completely randomized design (CRD), namely one treatment factor with the addition of vegetable oil concentrations of 30%, 25%, and 20%. The data were analyzed using variance, if the results were significantly different, then it was further tested with DMRT with a significant level of 5%. The results showed that the concentration of vegetable oil on shelf life and quality of shallot paste were not significantly different so that the addition of vegetable oil concentration had no effect on shelf life and quality of shallot paste. Panelists preferred color and taste parameters of shallot paste with the addition of 30% vegetable oil. Meanwhile, for the pasta aroma that the panelists like, the paste with the addition of 25% and 20% vegetable oil.